Can students learn from their co-students about tuberculosis? Outcomes from student-friendly quasi-experimental intervention study in India - B Priscilla Rebecca; Dhanalakshmi Angamuthu; Basilea Watson; E Thomas Beena; S Balaguru; Jacob Premkumar; Chandra Suresh; Nagarajan Karikalan (Wolters Kluwer Medknow Publications, 2022)
Background: The World Health Organization's "End TB Strategy" aims to end global tuberculosis (TB) epidemic through a holistic combination of health and social interventions placing the patients and communities at the heart of the response. This study aimed to assess the effectiveness of utilizing school children as ambassadors in TB advocacy. Materials and Methods: We adopted a quasi-experimental intervention design where students' awareness level was assessed before and after the intervention. A total of 185 student ambassadors were trained to conduct interventions in schools, and 920 students were randomly selected to assess the impact of the ambassador's intervention. A structured questionnaire was used to assess the correct and incorrect knowledge on specific aspects of TB. This intervention study was implemented in a phased manner which involved a participatory formative phase. A student-friendly and culturally relevant educational materials and activities for providing TB knowledge for the study student population were developed. Data collected from the baseline and end-line evaluation surveys were analyzed using STAT Ver. 16.0.- Stata Corp., June 2016, USA. Results: A significant increase (>80%; P < 0.05) in the correct knowledge on diagnosis and prevention for TB was noted among sampled students (n = 818) before and after intervention. Reduction in incorrect knowledge, like understanding TB as hereditary disease, was found to be less (50%; P < 0.05). Conclusions: School students lead intervention could significantly improve correct knowledge on TB and could be replicated.